IMPLEMENTATION OF JOYFULL LEARNING METHOD IN DEVELOPING STUDENTS' ENTHUSIASM FOR LEARNING IN ISLAMIC EDUCATION LESSON - Chotijah Maulidiah; Septiani Hidayatul Atiqo’; Ika Widiyawati (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
This study aims to describe the implementation of the joyfull learning method in developing student’s enthusiasm for learning in Pendidikan Agama Islam (PAI). Pendidikan Agama Islam (PAI) learning activities using joyfull learning methode can develop enthusiasm for learning in student, because based on the experience that has been carried out by PAI subject teachers throught the application of the lecturer method in the learning process student get bored easily which makes learning not conducive. Therefore, by applying the joyfull learning method, it can create enthusiasm for learning in student with an effective and fun learning atmosphere. This study uses qualitative methodes, in determining research subjects using purposive techniques. The data collection uses observation, semi-structured interviews, and documentation. Data analysis uses a model from Miles, Huberman and Saldana wich includes: data condensation,data presetation, and conclusions. Data validity was tested by technique triangulation and source triangulatoin. The result of this study showed that the implementation of the joyfull learning method in developing student’s enthusiasmfor learning in PAI. Subject was quite good and successful. Seen from the interview data conducted with students, the implementation.